Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires